2017
DOI: 10.1038/srep45261
|View full text |Cite
|
Sign up to set email alerts
|

Stability of R2* and quantitative susceptibility mapping of the brain tissue in a large scale multi-center study

Abstract: Multi-center studies are advantageous for enrolling participants of varying pathological and demographical conditions, and especially in neurological studies. Hence stability of the obtained quantitative R2* and susceptibility in multicenter studies is a key issue for their widespread applications. In this work, the stabilities of simultaneously obtained R2* and susceptibility are investigated and compared across 10 sites that are equipped with the same scanner and receiver coil, the same post-processing proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
6
16
0
1
Order By: Relevance
“…We found QSM is higher in the SN only in middle‐ and later‐stage patients, consistent with reports that increased iron is observed in advanced‐stage PD patients . However, our study did not detect significant longitudinal changes in QSM, possibly because QSM is less stable than R2* despite having a better signal for iron . The fact that R2* changes in the SNc persisted even after adjusting for QSM suggests that R2* may capture, in addition to iron, the complex microstructural changes occurring during PD progression.…”
Section: Discussionsupporting
confidence: 89%
“…We found QSM is higher in the SN only in middle‐ and later‐stage patients, consistent with reports that increased iron is observed in advanced‐stage PD patients . However, our study did not detect significant longitudinal changes in QSM, possibly because QSM is less stable than R2* despite having a better signal for iron . The fact that R2* changes in the SNc persisted even after adjusting for QSM suggests that R2* may capture, in addition to iron, the complex microstructural changes occurring during PD progression.…”
Section: Discussionsupporting
confidence: 89%
“…The variance in the QSM‐based CBV estimates was larger than that using the R 2 * method, but the average and median values were similar to R 2 *‐based estimates in GM and WM. A recent report from a multi‐center study showed higher stability in R 2 * than in QSM susceptibility measurements in brain mapping applications . That finding correlates well with our observations.…”
Section: Discussionsupporting
confidence: 80%
“…The variability found between QSM solvers and QSM‐based measures in this and other studies make the R 2 *‐based CBV method the recommended approach for CBV estimates, although in theory QSM approaches provide a more direct relationship to contrast agent concentration than R 2 * mapping and are less prone to artifacts that can vary with image parameters. This should continue to serve as motivation for development of improved QSM algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is the lack of test‐retest reliability analysis of the presented techniques. Nevertheless, previous studies found that QSMs have excellent reproducibility on intrascanner and interscanner acquisitions . In addition, previous studies exploring microvascular QSM‐OEF using hyperventilation found good reproducibility between 2 repeated hyperventilation challenges: Bland‐Altman plots revealed no statistically significant bias between the 2 sessions.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, previous studies found that QSMs have excellent reproducibility on intrascanner and interscanner acquisitions. [59][60][61][62] In addition, previous studies exploring microvascular QSM-OEF using hyperventilation found good reproducibility between 2 repeated hyperventilation challenges 11 : Bland-Altman plots revealed no statistically significant bias between the 2 sessions. Therefore, we believe that it is reasonable to infer that our hypercapnic QSM-OEF results would have very good intrasubject reproducibility.…”
Section: Discussionmentioning
confidence: 97%